KEADILAN DALAM PERSPEKTIF SOSIOLOGI HUKUM (ANALISIS SOSIOLOGI HUKUM TERHADAP KEADILAN DI INDONESIA) - Rewapatara, Hendrik Rikarsyo; Firman (CENDERAWASIH CONSTITUTIONAL REVIEW, 2025)
This paper examines the concept of justice from the perspective of sociology of law in Indonesia, emphasizing the importance of understanding justice that goes beyond positive law and integrates social values and community behavior. The introduction explains that justice needs to be viewed from various dimensions, including sociological, to prevent injustice in legal practice. The research method used is doctrinal normative law, with conceptual and statutory approaches to analyze existing regulations. The findings indicate that many legal decisions do not reflect sociological justice, such as in cases of corruption and environmental violations. Ideal justice must be derived from the values that develop within society, rather than solely based on legal texts. The author emphasizes the need for the actualization of justice grounded in the philosophical and sociological values of Pancasila, as well as community participation in the legal process. The conclusion suggests that law enforcement in Indonesia should consider sociological and moral aspects so that justice can be implemented and accepted in community life.